British Economic Development in South East Asia, 1880-1939 - Sunderland, David (London : Routledge, 2016)
'This collection focuses on the economic development of the areas of SE Asia with which Britain had a trading relationship. Covering 1880'1939, the economic growth of the region is revealed through a selection of rare primary resources organized thematically with sections dedicated to agriculture, mining, trade, labour, finance and infrastructure.'--Provided by publisher.
v. 1. General introduction. Agriculture -- v. 2. Mining, trade and industry -- v. 3. The building blocks of development : governance, transport and communciations, and human and financial capital. Index.
First published 2014 by Pickering & Chatto (Publishers) Limited.
Includes bibliographical references (pages 427-428) and index.
Keywords: Economic development -- Southeast Asia -- History -- 19th century -- Sources; Economic development -- Southeast Asia -- History -- 20th century -- Sources; Great Britain -- Commerce -- Southeast Asia -- History -- 19th century -- Sources; Great Britain -- Commerce -- Southeast Asia -- History -- 20th century -- Sources; Southeast Asia -- Commerce -- Great Britain -- History -- 19th century -- Sources; Southeast Asia -- Commerce -- Great Britain -- History -- 20th century -- Sources